The Effect of a Self-Efficacy-Enhancing Intervention on Perceived Self-Efficacy and Actual Adherence to Healthy Behaviours Among Women with Gestational Diabetes Mellitus - Al-Hashmi, Iman (Sultan Qaboos Univ Med J, 2018)
OBJECTIVES: This study aimed to evaluate the effectiveness of a self-efficacy-enhancing intervention (SEEI) on perceived self-efficacy and actual adherence to healthy behaviours among women with gestational diabetes mellitus (GDM). METHODS: This comparative pre-post study was conducted at the Antenatal Clinic of the Sultan Qaboos University Hospital, Muscat, Oman, between October 2016 and January 2017. A total of 90 adult Omani women with GDM were randomised to either a control group receiving standard prenatal care or a SEEI group. The SEEI group received an additional health education session and biweekly text messages to encourage adherence to healthy behaviours. All participants completed self-reported standardised questionnaires to determine perceived self-efficacy and actual adherence at baseline and after four weeks. RESULTS: At baseline, there were no significant differences between the control and SEEI groups in mean scores for perceived self-efficacy (122.9 ± 19.9 versus 118.2 ± 19.5; P = 0.26) or actual adherence to healthy behaviours (3.1 ± 1.2 versus 3.2 ± 1.0; P = 0.23). However, after four weeks, there was a significant positive difference between the SEEI and control groups in terms of pre-post change in scores for both perceived self-efficacy (9.9 ± 19.6 versus −1.8 ± 17.6; P <0.05) and actual adherence to healthy behaviours (1.5 ± 1.1 versus 0.4 ± 0.8; P <0.01). CONCLUSION: The SEEI was found to significantly improve perceived self-efficacy and actual adherence to healthy behaviours among a group of Omani women with GDM.